Elevated Circulating Levels of Inflammatory Markers in Patients with Acute Coronary Syndrome - Hamad Al Shahi; Kazunori Shimada; Katsumi Miyauchi; Takuma Yoshihara; Eiryu Sai; Tomoyuki Shiozawa; Ryo Naito; Tatsuro Aikawa; Shohei Ouchi; Tomoyasu Kadoguchi; Tetsuro Miyazaki; Hiroyuki Daida (International Journal of Vascular Medicine)
Objective. We evaluated inflammatory cytokines and chemokine in peripheral blood mononuclear cells (PBMCs) in patients with either acute coronary syndrome (ACS) or stable coronary artery disease (CAD). Methods. We enrolled 20 ACS patients and 50 stable CAD patients without previous history of ACS who underwent cardiac catheterization. Patients with an estimated glomerular filtration rate of ≤30 mL/min/1.73 m2 and C-reactive protein of ≥1.0 mg/dL were excluded. Blood samples were collected from the patients just before catheterization, and PBMCs were isolated from the whole blood. The levels of inflammatory cytokines and chemokine were measured by using real-time quantitative polymerase chain reaction and immunoassays. Results. The expression of tumor necrosis factor alpha (TNF-α), interleukin- (IL-) 6, IL-10, IL-23A, IL-27, and IL-37 was significantly higher in the ACS group than in the CAD group (P<0.05). In contrast, the expression of IL-33 was significantly lower in the ACS group than in the CAD group (P<0.05). The ACS patients had higher plasma levels of TNF-α, IL-6, and IL-10 in the ACS group than in the CAD group. Conclusion. Circulating levels of pro-/anti-inflammatory cytokines, including IL-23A, IL-27, IL-33, and IL-37, may be associated with the pathogenesis of atherosclerosis in ACS patients.